Patent Citations and the Geography of Knowledge Spillovers: A Reassessment - Thompson, Peter; Fox-Kean, Melanie (American Economic Review, 2005)
Patent Citations and the Geography of Knowledge Spillovers: A Reassessment by Peter Thompson and Melanie Fox-Kean. Published in volume 95, issue 1, pages 450-460 of American Economic Review, March 2005